2002
DOI: 10.1055/s-2002-30116
|View full text |Cite
|
Sign up to set email alerts
|

Saccharomyces Boulardii and Bacillus Cereus Var. Toyoi Influence the Morphology and the Mucins of the Intestine of Pigs

Abstract: The mode of action of probiotics is still incompletely understood. To study the interactions between probiotic micro-organisms and the host their effects on morphology and mucins of the intestinal mucosa were investigated. Fifteen clinically healthy weaned pigs were divided into three groups and received either Saccharomyces boulardii or Bacillus cereus var. toyoi or were left untreated. Sections of duodenum, proximal and mid jejunum, ileum, caecum, and colon were examined. An increase of villus length in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
37
0
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(41 citation statements)
references
References 25 publications
2
37
0
2
Order By: Relevance
“…Another hypothesis is that Bacillus cereus var. Toyoi spores seems to have a stabilising (decreasing) effect on the absorptive and secretory properties of pig jejunum (Lodemann et al 2008), on enterobacterial growth and selected metabolic parameters in digesta (Jadamus et al 2002) and on the intestinal architecture of weaning pigs (Baum et al 2002). Moreover, similar implications have been published by Kyriakis et al (1999), who indicated that the use of the same probiotic in weaning pigs reduced the incidence and severity of PWDS caused mainly by ETEC-strains, reduced mortality and improved the performance parameters.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…Another hypothesis is that Bacillus cereus var. Toyoi spores seems to have a stabilising (decreasing) effect on the absorptive and secretory properties of pig jejunum (Lodemann et al 2008), on enterobacterial growth and selected metabolic parameters in digesta (Jadamus et al 2002) and on the intestinal architecture of weaning pigs (Baum et al 2002). Moreover, similar implications have been published by Kyriakis et al (1999), who indicated that the use of the same probiotic in weaning pigs reduced the incidence and severity of PWDS caused mainly by ETEC-strains, reduced mortality and improved the performance parameters.…”
Section: Discussionmentioning
confidence: 66%
“…Toyoi spores, such as Toyocerin ® in sows (Alexopoulos et al 2001, 2004a,b, Taras et al 2005, Stamati et al 2006 or pigs of other ages (Baum et al 2002, Kyriakis et al 2003. There are also quite a few studies, proving the efficiency of probiotics during the post-weaning period, but there are only scarce published data referring to trials with the use of combination of benzoic acid and probiotics containg Bacillus cereus var.…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, Baum et al [17] also found that villus length was greater in the small intestine of piglets fed yeast than controls. In addition, it was indicated that longer villi are correlated with activation of cell mitosis [18] .…”
Section: Discussionmentioning
confidence: 85%
“…Because pronounced effects of probiotic microorganisms on intestinal mucosa morphology have been shown previously (Klein and Schmidts, 1997;Baum et al, 2002) these hypothesis was studied carefully within the project. A clarification of these kinds of effects was particularly important because the observations indicated an increase in villus height and mucosa surface in the jejunum of probiotic treated pigs which could be an influencing factor on nutrient absorption.…”
Section: Resultsmentioning
confidence: 99%